2005
DOI: 10.1039/b500852b
|View full text |Cite
|
Sign up to set email alerts
|

The metabonomics of aging and development in the rat: an investigation into the effect of age on the profile of endogenous metabolites in the urine of male rats using 1H NMR and HPLC-TOF MS

Abstract: The effect of aging and development in male Wistar-derived rats on the profile of endogenous metabolites excreted in the urine was investigated using both (1)H NMR spectroscopy and HPLC-TOF MS using electrospray ionisation (ESI). The endogenous metabolites were profiled in samples collected from male rats every two weeks from just after weaning at 4 weeks up to 20 weeks of age. Multivariate data analysis enabled clusters to be visualised within the data according to age, with urine collected at 4 and 6 weeks s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
112
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 34 publications
13
112
0
7
Order By: Relevance
“…A multiplatform study confirmed the enriched fatty acid metabolism of the db/db mouse by revealing increased transcript levels of fatty acid metabolism-associated carnitine palmitoyltransferase in the liver and higher urinary carnitine levels, measured using LC-MS (Gipson et al 2008). Furthermore, increased carnitine levels with age were observed in db/db but not in control mice, and similar age-dependent increases in carnitine were also reported in non-diabetic rats (Williams et al 2005b). Increased fatty acid metabolism results from a higher rate of lipolysis in adipose tissue and might exacerbate insulin resistance in liver and muscle tissue (Delarue & Magnan 2007).…”
Section: Genetic Rodent Models Of Diabetessupporting
confidence: 53%
“…A multiplatform study confirmed the enriched fatty acid metabolism of the db/db mouse by revealing increased transcript levels of fatty acid metabolism-associated carnitine palmitoyltransferase in the liver and higher urinary carnitine levels, measured using LC-MS (Gipson et al 2008). Furthermore, increased carnitine levels with age were observed in db/db but not in control mice, and similar age-dependent increases in carnitine were also reported in non-diabetic rats (Williams et al 2005b). Increased fatty acid metabolism results from a higher rate of lipolysis in adipose tissue and might exacerbate insulin resistance in liver and muscle tissue (Delarue & Magnan 2007).…”
Section: Genetic Rodent Models Of Diabetessupporting
confidence: 53%
“…43 Rapid changes in urine hippurate and 3-HPPA also were observed in young rats. 44 It is likely that the changes that we observed in aromatic metabolic species in dog urine are associated with establishment of a stable gut microbiota. In supporting this, we observed changes in urinary levels of aliphatic amines, including trimethylamine (TMA), DMA, DMG, and TMAO.…”
Section: Discussionmentioning
confidence: 96%
“…This methodology has also been applied in aging studies in several species including Caenorhabditis elegans, fruit fly, rodents, dogs, and humans (Kristal and Shurubor 2005;Mishur and Rea 2012). In mammalian studies, carnitines, fatty acids, and other metabolites associated with energy metabolism, lipid metabolism, nucleic acid metabolism, and oxidative stress were shown to be perturbed with age (Williams et al 2005;Granger et al 2007;Lu et al 2008;Lawton et al 2008).…”
mentioning
confidence: 99%